New records, neotype designation and DNA sequences of three species of Chaetonotus (Gastrotricha: Chaetonotidae) from Brazil - Salgado, Kelly Fernanda Acosta; Minowa, Axell Kou; Garraffoni, André Rinaldo Senna (Zootaxa, 2022)
Gastrotrichs are aquatic microinvertebrates (less than 1 mm long) commonly found in freshwater and marine environments worldwide. The taxonomy of gastrotrichs is mainly based on external morphological characters, such as body shape and size of the different body regions, presence and distribution of adhesive tubules, or the microstructure of the external cuticle (e.g. scales, spines, cephalic plates). The diversity of Gastrotricha is still poorly known, especially in tropical regions. The aim of this study is to use integrative taxonomy to report new records of Chaetonotus dadayi, C. paucisquamatus and C. furcatus from the states of São Paulo and Minas Gerais, Brazil. In this study we present 1) new records of C. dadayi in Brazil with new morphological information and a first-time comprehensive diagnosis of the species; 2) the redescription of C. paucisquamatus based on material collected at the type locality and the neotype designation; and 3) the first record of C. furcatus outside its type locality. We also discuss the actual occurrence of C. paucisquamatus and C. furcatus in Poland, given that both species were found in artificial environments with flora imported from South America.